3
$\begingroup$

I have a slight confusion with the notation $f(x)(y)$.

Does $f(x)(y)$ mean the same as $f(x,y)$?

Or does it mean something else?

Particularly I saw the notation $f(x)(y)$ in the following definition for Eulerian derivative of a functional $J: \Omega \rightarrow J(\Omega)$ to the direction of the vector field $V$:

$$dJ(\Omega;V) = \lim_{t\rightarrow 0}\frac{J(\Omega_t)-J(\Omega)}{t}$$

where $\Omega_t = T_t(V)(\Omega).$

$\endgroup$
  • $\begingroup$ If i read $f(x)(y)$, I would assume that $f$ is a map, which maps into a space of functions. $\endgroup$ – MooS Mar 22 '17 at 12:02
3
$\begingroup$

Let $X$, $Y$ and $Z$ be sets. Suppose that you are given a map $f \colon X \to Z^Y$, where $Z^Y$ is the set of all maps $Y \to Z$. Then, for any $x \in X$, it is legitimate to denote by $f(x)$ the map that sends $y \in Y$ to $f(x)(y) \in Z$.

This is, in particular, the case of derivatives, where at each differentiability point (x) of a function $J$ you want to attach a (linear) map $dJ(x)$ that acts again on points. Anyway, the derivative of $J$ at $x$ along $y$ is often denoted by $dJ(x;y)$, especially on old textbooks.

$\endgroup$
  • $\begingroup$ So it's a map from one set $X$ to functions between two sets $Y \rightarrow Z$? $\endgroup$ – mavavilj Mar 22 '17 at 12:11
  • $\begingroup$ @mavavilj Yes, this should be the standard interpretation. $\endgroup$ – Siminore Mar 22 '17 at 12:11
1
$\begingroup$

They almost mean the same thing: functions given sets $X,Y,Z$, there is a natural correspondence between functions $X \times Y \to Z$ and functions $X \to Z^Y$, where $Z^Y$ is the set of functions from $Y$ to $Z$. The translation between such kinds of functions is known as (un)currying, and is particularly important to computer scientists.

Specifically, given a function $f : X \to Z^Y$, we can define a new function $\widehat f : X \times Y \to Z$ defined by $\widehat f(x,y) = f(x)(y)$. Note that for each $x \in X$, $f(x)$ is a function from $Y$ to $Z$.

Conversely, given a function $g : X \times Y \to Z$, we can define a new function $\widetilde{g} : X \to Z^Y$ defined by letting $\widetilde{g}(x)$ be the function $Y \to Z$ defined by $\widetilde{g}(x)(y) = g(x,y)$.

This correspondence arises for the same reason that, for statements $p,q,r$, the implication $p \wedge q \Rightarrow r$ holds if and only if the implication $p \Rightarrow (q \Rightarrow r)$ holds. The underlying reason is that $Z^Y$ and $q \Rightarrow r$ are both examples of exponential objects.

This may have been more detail than you were looking for, but I hope it's helpful nonetheless.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.